2001
DOI: 10.1183/09031936.01.00049201
|View full text |Cite
|
Sign up to set email alerts
|

Expression of matrix metalloproteinases in pigs with hyperoxia-induced acute lung injury

Abstract: The aim of this study was to determine the role of matrix metalloproteinases (MMPs) in the pathogenesis of acute lung injury induced by hyperoxia.Twenty-three pigs were exposed in sealed cages to w80% oxygen (for 24-120 h) or room air. Correlation between MMP-2/MMP-9 activity, measured by gelatin zymography in bronchoalveolar lavage fluid (BALF), and the histological findings and pathological parameters were examined in detail. Sources of these MMPs in the hyperoxic lung were analysed by immunohistochemistry.T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 29 publications
5
35
0
2
Order By: Relevance
“…In hyperoxia-treated pigs, animals developed features of lung injury such as increased wet-to-dry ratio, decreased Pa,O 2 :FI,O 2 ratio and increased bronchoalveolar lavage (BAL) fluid cellularity after 72 h of exposure to 80% oxygen [21]. This was associated with elevated MMP-9 and -2 in BAL after 72 h; parameters of lung injury correlated dose-dependently with BAL MMP-9 concentrations.…”
Section: In Vivo Modelsmentioning
confidence: 80%
See 1 more Smart Citation
“…In hyperoxia-treated pigs, animals developed features of lung injury such as increased wet-to-dry ratio, decreased Pa,O 2 :FI,O 2 ratio and increased bronchoalveolar lavage (BAL) fluid cellularity after 72 h of exposure to 80% oxygen [21]. This was associated with elevated MMP-9 and -2 in BAL after 72 h; parameters of lung injury correlated dose-dependently with BAL MMP-9 concentrations.…”
Section: In Vivo Modelsmentioning
confidence: 80%
“…It was also noted that elevated MMP-2 levels were detected earlier than MMP-9, with a peak at 72 h in contrast to 96 h for MMP-9. Immunohistochemistry localised MMP-9 to neutrophils, macrophages and epithelial cells, whereas MMP-2 mainly localised to alveolar macrophages [21]. Notably, the dominant form of both MMP-2 and-9 detected was the high molecular weight (MW) latent form.…”
Section: In Vivo Modelsmentioning
confidence: 99%
“…In these studies, we concluded that resuscitation with 100% O 2 subsequent to global hypoxia increases cerebral and myocardial injury compared with resuscitation with 21% O 2 . Increased MMP activity was investigated previously in a hyperoxic piglet pulmonary injury model but only after 72 h of exposure (11). Hypoxia-reoxygenation injury triggers MMP production earlier than just hyperoxia (28).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the roles of these proteinases in acute lung injury. However, their precise contribution in the development of acute hyperoxic lung injury, including the relationship among MMPs, severity of disease, and pathologic changes, is still unclear (11). MMPs play a role in the increased pulmonary permeability and inflammation after oxidative stress.…”
mentioning
confidence: 99%
“…MMP-9 and MMP-2 appear to be central to the acute phases of ARDS; lung injury models demonstrate increases in their concentrations in BAL fluid following injury [104] (although this study did not report efforts to standardise the assay by measuring total protein content of different samples). This has been further supported by demonstration of increases following bleomycin injury in rats [105] and in a pig model of lung injury after cardiopulmonary bypass [106].…”
Section: Pathogenesis Of Ardsmentioning
confidence: 99%